Thoughts About the Complement Clause Subject Being Assigned with Genitive Case in Old Turkic (Orkhun and Uighur) I - Çiçekler, Ahmet Naim (FSM Vakıf Üniversitesi, 2015)
In this study, it will be analyzed that the inner clause subject is assigned with genitive case in Old Turkic, which is the first period of Turkish language. In Modern Turkish, the assignment of inner clause subject is made by the head modifier, whereas it is made by the head determiner in Dagur and Modern Uigur. According to this classification made by Miyagawa (2008), it will be analyzed in this study whether Old Turkic is a C-licensing or a D-licensing language. Furthermore, the state of the inner clause subject being assigned with genitive case in Old Turkic will be compared with genitive case assignments in Modern Turkish, Old Anatolian Turkish, and Modern Uigur.
Eski Türkçede İçcümlenin Öznesinin Genitif Durum ile Yüklenmesi Üzerine Düşünceler I
Keywords: Old Turkic; Genitive Case; Case Assignment; C-licensing; D-licensing; Eski Türkçe; Genitif durum; Durum yükleme; Tüm-yetkilendirme; Bel-yetkilendirme